1, 2, 3 Johannes: ’n Oorsig oor die huidige stand van navorsing rakende inleidingsvraagstukke - Watt, Jan G. van der (HTS Teologiese Studies / Theological Studies, 2011)
This article has presented an overview of the most important positions taken on certain introductory issues related to 1, 2 and 3 John. The article has not focussed on the detailed discussion of problems, but has rather provided a broad overview of the most important current positions. A typical characteristic of the introductory questions is their interrelatedness. The research inter alia examined the way in which decisions about the relation between the Gospel and Letters of John influence the question of authorship or the place and date of the Letters and how decisions about the level of conflict in the Letters influence their sequence.
free